The Quality of Services and Their Impact on Customer Satisfaction in the Telecom Sector with Reference to Mobile Service Providers - Mann, Puja Walia; Jha, Manish (Indian Journal of Marketing, 2015)
The research is based on the quality of services that are being offered by various mobile service providers and the level of satisfaction that the customers experience. The government launched the mobile phone services and opened it for the private operators 10 years back. With this move of the government, many big and small companies ventured into the business. However, as we move on today, after 10 years, only half of the companies are surviving in the industry. The rate of addition of new subscribers is equalized or balanced by the churning of the customers. According to the Telecom Regulatory Authority of India (TRAI), mobile telephony service providers have failed to meet the set customer satisfaction benchmarks. In an attempt to reduce the churn rate problem, companies constantly try to come up with new ideas and plans to retain their original customers and attract new customers. The objective of the study was to assess the quality of services provided by basic and cellular mobile service providers for assessing the customers’ perceptions of the services. The aim of this research was to measure the overall satisfaction of the customers with regard to network availability, billing problems, customer care services, usage, etc.